Playing, Learning, and Entrepreneurship: Exploring the Kid’s Market Day Experience in Entrepreneurship Education for Elementary School Students: Bermain, Belajar, dan Berwirausaha: Menyelami Pengalaman Kid’s Market Day dalam Pendidikan Kewirausahaan Anak SD - Fanaturiza, Yopi Agusta; Fahyuni, Eni Fariyatul (Indonesian Journal of Innovation Studies, 2026)
General Background Fostering entrepreneurial mindsets from early childhood builds crucial skills such as creativity, problem-solving, and adaptability for future economic challenges. Specific Background Although the Merdeka Curriculum provides flexibility for practical learning, elementary schools often lack structured models to effectively cultivate entrepreneurial competencies. Knowledge Gap Limited empirical research addresses the integration of learning, playing, and entrepreneurship within elementary education frameworks. Aims This qualitative phenomenological study explores the execution of the Kid’s Market Day program at SD Negeri Gebang 2 Sidoarjo to examine its implementation and operational challenges. Results Findings show that the experiential initiative strengthens critical thinking, team collaboration, and communication skills through direct sales, product creation, and door-to-door promotion. Novelty This work establishes a practical model combining play-based pedagogy and hands-on business activities tailored for young learners. Implications The model offers strategic insights for educators to design holistic entrepreneurial curricula while resolving resource constraints. Key Findings Highlights Implementation of the Kid’s Market Day program advances critical thinking, teamwork, and communication competencies among elementary students through interactive project activities. Practical business execution, including direct product creation, money management, and door-to-door promotional outreach, fosters practical commercial understanding in early learners. Strategic communication, adaptive scheduling, and collaborative engagement effectively address institutional obstacles such as constrained budgets, teacher training gaps, and parental hesitancy. Keywords: Market Day, Entrepreneurship Education, Elementary School, Experiential Learning, Pedagogy